(untitled) (Revista Iberoamericana de Bioética, 2025)
In recent years, the participation of women in medical training has increased substantially, which has led to consider that the profession is undergoing a process of feminization. However, this article presents, from a series of testimonies of medical professionals in training —residents and undergraduate interns—, elements that allow us to recognize the permanence and reproduction of gendered logics anchored to the Masculine. These logics have been historically elaborated and sedimented, acquiring cultural legitimacy within the profession and becoming moral demands during the training process. This conglomerate, which in this article is referred to as the medical palimpsest, shapes the moral dispositions of physicians-in-training, regardless of their sex, gender identity or other identity coordinates. To account for the medical palimpsest represents the possibility of contributing to clinical bioethics from a critical gender perspective.